2004
DOI: 10.1073/pnas.0408159101
|View full text |Cite
|
Sign up to set email alerts
|

Inhaling to mitigate exhaled bioaerosols

Abstract: Humans commonly exhale aerosols comprised of small droplets of airway-lining fluid during normal breathing. These ''exhaled bioaerosols'' may carry airborne pathogens and thereby magnify the spread of certain infectious diseases, such as influenza, tuberculosis, and severe acute respiratory syndrome. We hypothesize that, by altering lung airway surface properties through an inhaled nontoxic aerosol, we might substantially diminish the number of exhaled bioaerosol droplets and thereby provide a simple means to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
340
3
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(385 citation statements)
references
References 25 publications
25
340
3
13
Order By: Relevance
“…Reduced virus shedding was also observed in ferrets inoculated IN with a low or intermediate dose of TH16 virus compared with similar AR inoculations. A possible explanation is that the 1-mL volume of inoculum alters the surface tension of the mucous layer lining the respiratory tract, and such alteration in surface tension has been shown to result in reduced virus shedding (25), although this effect seems to be overcome by increasing the viral load in the IN inoculum. Ferrets inoculated via AR with TH16 virus exhibited a broader spectrum of disease than IN-inoculated animals, but lethality was similar.…”
Section: Discussionmentioning
confidence: 97%
“…Reduced virus shedding was also observed in ferrets inoculated IN with a low or intermediate dose of TH16 virus compared with similar AR inoculations. A possible explanation is that the 1-mL volume of inoculum alters the surface tension of the mucous layer lining the respiratory tract, and such alteration in surface tension has been shown to result in reduced virus shedding (25), although this effect seems to be overcome by increasing the viral load in the IN inoculum. Ferrets inoculated via AR with TH16 virus exhibited a broader spectrum of disease than IN-inoculated animals, but lethality was similar.…”
Section: Discussionmentioning
confidence: 97%
“…It is worth noting that Edwards et al 7 showed that delivering an aerosolised surfactant solution to the lungs increases exhaled aerosol concentration during normal breathing 30 fold. Surfactants have a well known ability to increase aqueous film elasticity, thereby allowing bubbles to form readily and to achieve much larger diameters before bursting.…”
Section: Interpretation Of the Results In Terms Of The Aerosol Formatmentioning
confidence: 99%
“…That model does not adequately explain the influence that respiratory activities exert on aerosol concentration: Experimental data do not show a clear increase in aerosol concentration with exhalation flow rate during breathing, as should occur if turbulent airflow is the dominant breath aerosol formation mechanism. In fact normal breathing can produce higher aerosol number concentrations than coughing 4,6,7 which involves far higher flow rates. Gebhart et al 8 found that these particles are expired from volumetric lung depths of more than 200 cm -3 implying that they occur beyond the conducting airways.…”
Section: Introductionmentioning
confidence: 99%
“…Such variability has already been mentioned [11,23] and may be linked to high inter-subject variability in the number of small-size particles produced during mouth breathing [24], possibly relating to the physical properties of the lung lining fluid [25]. Several mechanisms have been described to explain the retention properties of filters in terms of particle size.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measured resistance of such filters is found to be slightly higher [26] and the experimental design is far from the conditions of natural contamination occurring in pulmonary function testing. In particular, the droplets produced by this experimental condition (3-5 mm) are much larger than the droplets (,1 mm) produced by normal breathing [25] and even coughing [24]. During standard spirometry, the SensorMedics filter was considered no different from the Pall filter [27].…”
Section: Discussionmentioning
confidence: 99%